Accelerating the convergence of Newton-type iterations - Tugal Zhanlav; Ochbadrakh Chuluunbaatar; Vandandoo Ulziibayar (Journal of Numerical Analysis and Approximation Theory, 2017)
In this paper, we present a new accelerating procedure in order to speed up the convergence of Newton-type methods. In particular, we derive iterations with a high and optimal order of convergence. This technique can be applied to any iteration with a low order of convergence.